2017
DOI: 10.1001/jamadermatol.2017.2815
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Pubic Hair Grooming–Related Injuries and Identification of High-Risk Individuals in the United States

Abstract: IMPORTANCE Pubic hair grooming is a common practice that can lead to injury and morbidity.OBJECTIVE To identify demographic and behavioral risk factors associated with pubic hair grooming-related injuries to characterize individuals with high risk of injury and develop recommendations for safe grooming practices. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study conducted a national survey of noninstitutionalized US adults (aged 18-65 years). The web-based survey was conducted through a probability-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 22 publications
(61 reference statements)
3
23
0
9
Order By: Relevance
“…6,8,12 Pubic hair removal is associated with high rates of side effects, such as lacerations, itching, folliculitis, rashes and burns. 7,11,[13][14][15][16] A cross-sectional web-based national survey in the US found that over a quarter of the women who had ever groomed reported sustaining injuries such as lacerations, burns and rashes. 14 Between 2002 and 2010, the number of genitourinary injuries related to grooming practices had increased fivefold in an emergency department setting in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,12 Pubic hair removal is associated with high rates of side effects, such as lacerations, itching, folliculitis, rashes and burns. 7,11,[13][14][15][16] A cross-sectional web-based national survey in the US found that over a quarter of the women who had ever groomed reported sustaining injuries such as lacerations, burns and rashes. 14 Between 2002 and 2010, the number of genitourinary injuries related to grooming practices had increased fivefold in an emergency department setting in the US.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,[13][14][15][16] A cross-sectional web-based national survey in the US found that over a quarter of the women who had ever groomed reported sustaining injuries such as lacerations, burns and rashes. 14 Between 2002 and 2010, the number of genitourinary injuries related to grooming practices had increased fivefold in an emergency department setting in the US. 15 Ever having groomed has been positively associated with a history of self-reported sexually transmitted infections (STIs) after adjusting for age and number of lifetime sexual partners.…”
Section: Introductionmentioning
confidence: 99%
“…Pubic hair grooming could lead to increased STI risk via the sharing of grooming tools with an infected individual; however, fomite transmission of GC or CT has never been documented [7]. Grooming–especially frequent grooming and removal of all pubic hair–can cause injury [10]. The process of stripping away pubic hair could cause microtrauma in the skin’s mucocutaneous barrier, thereby facilitating pathogen entry and transmission [11].…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 summarizes three studies conducted on grooming practices in the United States. Two were conducted using female panelists (70, 71), and one was conducted among women and men (72). All three studies determined that the most popular methods of pubic hair removal among women is a non-electric razor (~60–90% of groomers).…”
Section: Unique Habits and Practices Effecting Genital Skinmentioning
confidence: 99%
“…All three studies determined that the most popular methods of pubic hair removal among women is a non-electric razor (~60–90% of groomers). In the study that included men as subjects it was determined that both non-electric and electric razors were commonly used for pubic hair removal (30.1 and 35.9%, respectively) (72).…”
Section: Unique Habits and Practices Effecting Genital Skinmentioning
confidence: 99%